An enhanced New Product Development (NDP) model and the application of Taguchi Methods in upstream NPD activities - Bhardwaj, Vandita, 1971- (2000)
Thesis (M.Eng.)--Memorial University of Newfoundland, 2000. Engineering and Applied Science Bibliography: leaves 186-190.